Juridical Review of Legal Protection for Victims of Mobile Malware Attacks Through Digital Invitations - Arif Budianto; Surya Nita (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This research aims to analyze the characteristics of mobile malware attacks through digital invitations, evaluate legal regulations that protect victims in the Banten Police area, and identify obstacles and formulate solutions to improve the effectiveness of legal protection against cybercrime. With increasing cases of cybercrime in the region, this research combines a multidisciplinary approach through field research and normative legal research. Data were obtained from three main sources, namely interviews with victims, law enforcement officials, and legal experts (primary sources); official documents such as laws and regulations (secondary sources); and additional related literature (tertiary sources). Data collection techniques were conducted through observation, in-depth interviews, and documentation, which were then analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that mobile malware attacks through digital invitations, which utilize phishing, smishing, and vishing techniques, have become a serious threat with a significant impact on financial security and user data privacy. Existing regulations, such as the Electronic Information and Transaction Law and the Personal Data Protection Law, still have limitations in providing effective protection, especially in the Banten Police area. The main obstacles identified include an imbalance in regulatory focus that focuses more on punishing perpetrators, a lack of technological infrastructure, and low public awareness of cyber threats. Therefore, this study recommends the need for regulatory revisions with an emphasis on victim protection, capacity building of law enforcement officers, public education on digital security, and international cooperation to deal with increasingly complex cybercrime.